Field testing and numerical modeling of vehicle-induced vibrations on an ancient seawall via an approach slab - Lin, Wei; Chen, Qiang; Hu, Min; Xu, Yangyang; Liu, Benyong; Shi, Li (Frontiers in Earth Science, 2025)
The Yanguan Ancient Seawall at the Qiantang River estuary is a nationally protected cultural heritage and an in-service flood defense. Construction activities, such as vehicle crossings, pose risks of vibration-induced damage to this aging structure. In this study, a three-dimensional finite element model was developed to evaluate the vibrations caused by moving vehicles on the seawall. The model represents the seawall’s discrete-continuum structural characteristics by modeling rubble stone blocks with solid elements and bonding mortar with cohesive zone elements. Additionally, a custom Vehicle-Road Interaction element was introduced to simulate both vertical and tangential wheel–road contact forces for vehicles crossing the inclined approach slab. Field vibration measurements were used to validate the model, demonstrating that it can accurately reproduce the observed vibration response. The validated model was then applied to investigate the seawall’s vibration behavior under various approach slab inclination angles. The results provide a scientific basis for designing vibration mitigation measures and inform strategies to protect this cultural heritage structure.